2015
DOI: 10.12816/0017517
|View full text |Cite
|
Sign up to set email alerts
|

Predilection for Junk Food Consumption among 15-Year-Old School Children in North Chennai , India

Abstract: Junk food culture has a vigorously uprising trend among youngsters and it makes people eat without planning. They eat not only during pre-set mealtime, but also in the leisure time (1,2,3). A food that is high in fat, sodium, and/or sugar, provides high calories, but is of no value, is generally known as a "junk food." Junk food seems attractive and is easy to prepare, carry, purchase, and consume. Common junk food includes fast food (burgers, pizzas, patties, nuggets, and so forth), chips, candy, sweet desser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Kuhi et al also found a significant and positive association between exposure to advertisements and fast food consumption; those who were more exposed to advertisements, had eaten more fast food [39]. In the study of Purushothamanet al, all of adolescents reported that advertisements influenced them to eat more junk foods [40]. According to the results of current study and other similar studies, it can be stated that the media and their food advertisement have very important role in adolescents' eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…Kuhi et al also found a significant and positive association between exposure to advertisements and fast food consumption; those who were more exposed to advertisements, had eaten more fast food [39]. In the study of Purushothamanet al, all of adolescents reported that advertisements influenced them to eat more junk foods [40]. According to the results of current study and other similar studies, it can be stated that the media and their food advertisement have very important role in adolescents' eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, the causes of dramatic increase in consumption of junk food in adolescents are the taste change, quick and easy access, being delicious, family structure, low cost, and tendency to these foods (9). Other studies have mentioned the roles of factors such as family and peers in the acquisition of nutrition knowledge and in taking measure to conduct a nutritional behavior (8,10,11).…”
Section: Introductionmentioning
confidence: 99%